Monofonik Türk Makam Müziğinde İşitsel Melodi Kestirimi - ŞİMŞEK, BERRAK ÖZTÜRK; Akan, Aydın (IEEE, 2020)
Bu çalışmada, monofonik Türk makam müziği eserlerinde baskın işitsel melodi çıkarımı için yeni bir yöntem önerilmiştir. Müzik sinyalleri, Geliştirilmiş Değişken Mod Ayrıştırma Yöntemi kullanılarak ayrıştırılır ve temel frekanslar, her moddaki merkez frekanslarının hesaplanmasıyla elde edilir. Baskın melodi hattını tahmin etmek ve seçmek için her penceredeki farklı frekans bilgilerinden bazı parametreler belirlenir. Elde edilen sonuçlar, batı müziği için kullanılan sinyal işleme algoritmaları olan YIN ve MELODIA ile karşılaştırılmıştır. Değerlendirme aşamasında uluslararası standartlara bağlı kalınarak MIREX kriterleri kullanılmaktadır. Simülasyon sonuçları, Geliştirilmiş Değişken Mod Ayrıştırma Yönteminin karşılaştırmada kullanılan diğer yöntemlere göre daha başarılı sonuçlar verdiğini göstermiştir.

In this study, a new method is proposed for predominant audio melody extraction in monophonic Turkish maqam music works. The music signals are decomposed using the Improved Variable Mode Decomposition Method and the fundamental frequencies are obtained by calculation of center frequencies on each mode. In order to estimate and selection of predominant melody line some parameters are determined from the different number of frequency information in each window. The obtained results are compared to YIN and MELODIA which are the signal processing algorithms used for western music. MIREX criterias are used in the evaluation step, adhering to international standards. Simulation results have shown that Improved Variable Mode Decomposition Method gives more successful results than other methods used in comparison.
Audio Melody Extraction from Monophonic Turkish Maqam Music
Audio Melody Extraction from Monophonic Turkish Maqam Music
Keywords: Monophonical Turkish Maqam Music; Melody Extraction; Improved Variational Mode Decomposition; Mirex Evaluation